Degradation kinetics of carpaine and antioxidant properties of dried Carica papaya leaves as affected by drying methods - Yap, Jing Ying; Hii, Ching Lik; Ong, Sze Pheng; Lim, Kuan Hon; Abas, Faridah; Pin, Kar Yong (Walter de Gruyter, 2022)
Carpaine in papaya leaves has the potential to treat dengue fever and it also contains antioxidants which could prevent or inhibit oxidation processes in the human body. Studies were conducted on the effects of storage on carpaine retention and antioxidant properties of dried papaya leaves. Results showed that the Weibull model could predict well the degradation kinetics of carpaine in all samples (freeze drying and hot air drying at 60 °C and 70 °C) except for hot air dried samples at 80 °C and shade dried samples (first order model). Generally, freeze dried samples showed the highest half-life whereas total polyphenols content and antioxidant properties (ABTS and DPPH free radical scavenging activities) of all dried samples decreased with storage period. An increasing trend in total colour difference (ΔE * ) was observed in all samples possibly due to chlorophyll degradation. It is thus recommended to select freeze dried samples for storage purpose due to better stability as indicated by the lowest rate constant (k = 0.0135 1/month) and the highest half-life (t1/2 = 51.2 months).